The Synergistic Effect of Co-delivery of Anticancer Drugs Into Astrocytes Isolated From Human Glioblastoma Multiforme - Hashemi, Mansoureh; Zali, Alireza (International Clinical Neuroscience Journal, 2020)
Background: Chemotherapy drugs are not effective in the treatment of primary brain tumors due to the low efficacy of these drugs and drug transfer from the blood-brain barrier (BBB) toward the tumor site. Our purpose in this study was to assess the co-delivery of anticancer drugs to increase drug permeability from BBB. Methods: In this study, two chemotherapy drugs, namely methotrexate (MTX) and paclitaxel (PTX), were inserted into polyvinyl alcohol and poloxamer188-conjugated nanoparticles (NPs). Astrocytes were treated with different concentrations of 0-50 μg/ml from MTX, PTX, the MTX-PTX mixture, PTX-loaded NPs, MTX-loaded NPs, and PTX-MTX co-loaded NPs for 48 hours. The tumoricidal effect was assessed using the survival rate, Hoechst staining, and western blotting. Results: The results indicated significant reduction of the survival rate in astrocytes treated with PTX-MTX co-loaded NPs. In addition, apoptosis hallmarks consisting of fragmented DNA, overexpression of Bax, and expression reduction of Bcl-2 were in the cultured astrocytes. Conclusions: Our study proposes that the PTX-MTX co-delivery to NPs could be used as a possible approach for anti-cancer drug delivery to glioblastoma multiforme.